THE EFFECT OF FREE CASH FLOW, COMPANY GROWTH AND PROFITABILITY ON DEBT POLICY ON MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Teguh Setiawan Wibowo; Lusy Lusy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Growing companies need funds that can be financed through debt. Several factors that influence debt policy include: free cash flow, company growth and profitability. This research is a quantitative research that takes data from BEI, a mining sector company from 2016 to 2018 with a population of 48 company data, using purposive sampling technique obtained as many as 15 company data. The conclusion from the results of this research shows that free cash flow, company growth and profitability as measured using return on assets, have a significant effect on debt policy. The debt policy variable in this research uses the Debt to Asset Ratio measurement. The results of the coefficient of determination obtained a value of 56.5% indicating that debt policy is influenced by free cash flow, company growth and profitability, while the other 43.5% is influenced by other variables not included in this research. Companies need to pay attention to other variables besides debt policy, such as Price Earnings Ratio, Dividend Payout Ratio and Tobin's Q. Keywords: free cash flow, company growth, profitability, debt policy